Estrogen Regulates Epithelial Cell Deformability by Modulation of Cortical Actomyosin through Phosphorylation of Nonmuscle Myosin Heavy-Chain II-B Filaments - Li, Xin (2006)
The objective of the study was to understand how estrogen modulates the rigidity of the cytoskeleton in epithelial cells. Estrogen depletion decreased, and treatment with 17β-estradiol increased deformability of cervical-vaginal epithelial cells. Estrogen also induced redistribution of nonmuscle myosin II-B (NMM-II-B); lesser interaction of NMM-II-B with actin; increased phosphorylation of NMM-II-B-heavy chains at threonine and serine residues; and decreased filamentation of NMM-II-B in vitro. The effects of 17β-estradiol were time and dose related and could be mimicked by diethylstilbestrol. The effects of estrogen were blocked by cotreatment with antisense oligonucleotide for the estrogen receptor-α and inhibited by ICI-182,780 and tamoxifen; omission of epithelial growth factor (EGF) from the culture medium; and cotreatments with the EGF receptor inhibitor AG1478, the ERK-MAPK inhibitor PD98059, the casein kinase-II (CK2) inhibitor 5,6-dichloro-1-β-(D)-ribofuranosylbenzimidazole, the Rho-associated kinase inhibitor Y-27632, and the nonspecific phosphatase inhibitor okadaic acid. Coadministration of 5,6-di-chloro-1-β-(D)-ribofuranosylbenzimidazole plus okadaic acid blocked the 17β-estradiol effect. H-89 or LY294002 did not significantly affect estrogen effects. Treatment with estrogen increased activation of ERK1/2 and CK2 activity. These data suggest a novel pathway of estrogen regulation of the cytoskeleton in epithelial cells. The effect is mediated by estrogen receptor-α and involves in part the EGF-EGF receptor and ERK-MAPK cascades as proximal signaling networks and the CK2 and Rho-associated kinase-regulated myosin heavy chain phosphatase as terminal effectors. Augmented phosphorylation of NMM-II-B can block filamentation and induce disassociation of the myosin from the cortical actin, and disruption of the actomyosin ring can increase cell deformability. This mechanism can explain estrogen regulation of paracellular permeability in cervical-vaginal epithelia in vivo.